2014
DOI: 10.1002/mrm.25111
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of rician noise in the analysis of biexponential transverse relaxation in cartilage using a multiple gradient echo sequence at 3 and 7 tesla

Abstract: Purpose Previous work has evaluated the quality of different analytic methods for extracting relaxation times from magnitude imaging data exhibiting Rician noise. However, biexponential analysis of relaxation in tissue, including cartilage, and materials, is of increasing interest. We therefore analyzed biexponential transverse relaxation decay in the presence of Rician noise and assessed the accuracy and precision of several approaches to determining component fractions and apparent transverse relaxation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 49 publications
5
57
0
Order By: Relevance
“…The sequence has had successful applications in sodium imaging 42,43 and ex-vivo Achilles tendon imaging 24 . In our study, the 3D cone UTE sequence provided complete anatomic coverage of the patellar tendon in human subjects at 3.0T with clinically feasible spatial resolutions and scan times and with an SNR of 54.5, which has been shown to be adequate to accurately estimate bi-component T2* parameters from previous literature 28 and the results of our simulation study. Recent studies have demonstrated that bi-component exponential signal models are better suited than single-component models for evaluating tendon 19,[23][24][25] .…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The sequence has had successful applications in sodium imaging 42,43 and ex-vivo Achilles tendon imaging 24 . In our study, the 3D cone UTE sequence provided complete anatomic coverage of the patellar tendon in human subjects at 3.0T with clinically feasible spatial resolutions and scan times and with an SNR of 54.5, which has been shown to be adequate to accurately estimate bi-component T2* parameters from previous literature 28 and the results of our simulation study. Recent studies have demonstrated that bi-component exponential signal models are better suited than single-component models for evaluating tendon 19,[23][24][25] .…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, previous studies have found a significant increase in short T2* in pathologic tendon when compared to normal tendon, which is specifically due to disruption of the highly organized collagen fiber network, but no significant difference in long T2* 25,39 . Accurate estimations of bi-component T2* parameters requires sufficient SNR and proper noise modeling which is particularly important when estimating pixel-by-pixel spatial variations across a tissue sample 28 . Both our simulation and in-vivo studies showed that T*2, l in tendon has much greater spatial variation, as indicated by the standard deviation of image voxels, and much higher sensitivity to noise when compared to T*2,s and fs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations